Emerging concepts in neuropathic and neurogenic itch - Kelsey L. Auyeung; Brian Kim (2023)
Chronic pruritus has multiple etiologies, ranging from inflammatory to metabolic and neuropathic processes. However, recent advances in itch biology have shed light on potential mechanisms that explain the molecular and cellular basis of these pathologies. Furthermore, new understanding of neuroimmune itch circuits necessitates clarification of terminologies such as "neuropathic" and "neurogenic." This review provides an overview of ways new concepts may better explain the pathophysiology of a variety of chronic pruritic disorders and the rationale for directing emerging novel therapeutic strategies toward them.